Ayurvedic management of Vicharchika (Lichen Simplex Chronicus) - A case report - Neelam Kumari Singh; Alok Singh Sengar; Bipin Bihari Khuntia (Indian Journal of Ayurveda and Integrative Medicine KLEU, 2023)
Lichen simplex chronicus (LSC) consists of lichenified scaly plaque due to chronic scratching. The available conventional treatments are various topical antipruritic agents and corticosteroids, which are associated with high rates of treatment failure and complications because trans-epidermal drug absorption is limited. LSC manifests as a significant challenge to a physician due to persistent itching and therapeutic resistance. In Ayurveda, this condition has a close resemblance to Vicharchika. Vicharchika is a type of Kshudra kustha with dominancy of Kapha dosha characterized by redness, itching, pain, cracks, and dryness. In this case report, a 48 year old female reported complaints of multiple black-colored patches on the dorsum surface of bilateral feet with severe itching for 6 years. Local examination revealed lichenified hyperpigmented plaques with erythematous bases and well-defined edges covered by white scales with central excoriation. Plaques were found bilaterally over the dorsum of feet and malleolus. Based on symptoms and signs, the case of LSC was diagnosed. This case was managed effectively with Ayurvedic internal medications such as Arogyavardhini Vati, Kaishore Guggulu, Nishaamlaki Vati, Triphala churna, Khadirarishta, and local application of Brihat Marichyadi oil and Sudha Gandhak. The outcome assessment was based on improvement in the size of skin patches, hyperpigmentation, thickening, and itching. Complete improvement has been observed in symptoms after 4 months of regular treatment. No adverse effect pertaining to the prescribed drug was reported during the study period. Ayurvedic medicines offer a good approach to managing LSC.